THE LIGATION OF INTERSPHINCTERIC FISTULA TRACT AS AN ALTERNATIVE TREATMENT FOR PERIANAL FISTULA AT TERTIARY CARE HOSPITAL: LIGATION OF INTERSPHINCTERIC FISTULA TRACT - Dal, Nawaz Ali; Katyar, Ishrat Raheem; Mallah, Mohammad Qasim; Laghari, Ahsan; Shaikh, Shiraz; Dalwani, Abdul Gafoor (LIAQUAT MEDICAL RESEARCH JOURNAL, 2021)
This study was aimed to evaluate clinical outcome of patients with perianal fistula operated with the ligation of intersphincteric fistula tract (LIFT) technique. The study was conducted at Department of Surgery, Liaquat University of Medical & Health Sciences, Jamshoro from July 2018 and August 2019. A total of 22 patients diagnosed with perianal fistula operated with the Ligation of Intersphincteric Fistula Tract (LIFT) technique were selected using non-probability consecutive sampling technique. Physical examination and magnetic resonance imaging (MRI) and/or endosonography (ES) were performed to make a confirmed diagnosis of fistula. They were classified according to Parks classification. All patients were subjected to intersphincteric fistulous tract ligation using the technique defined by Rojanasakul modified. There were 16 males and 6 females. Mean age was 42 years (range 23-68 years of age). Out of 22 patients, 17 patients had a history of perianal abscess drainage prior to surgery and an average preoperative symptom presentation was 2.2 years (range 0-10 years). Therapeutic success with first surgery was achieved in 77% and with a second surgery in 90%. None of this patients modified their preoperative Wexner. It was concluded that LIFT technique appears to be a convenient, reproducible, and effective surgical alternative. This provides an appropriate closing rate and without continence modification, Therefore indicated for complex cryptoglandular fistulas.